The knowledge of the medical students in the field of prevention, diagnosis, and the treatment of the Malignant Melanoma - Żelasko, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Malignant melanoma of the skin is a rising problem in the field of Oncology. As the years go on there has been a notable rise in the numbers of morbidity and deaths from this type of cancer. A significant cause of this rise could be assigned to the lack of general knowledge of the subject through the society, in the aspects of probability of appearance of the malignant melanoma of the skin, as well as late discovery of the changes of the skin. The diagnostic possibilities, and treatment options are becoming more and more effective. Profilactic programs focusing on this particular problem are being created throughout the world of medicine. Aim. The main objective of this essay is to gauge the range of knowledge of the medical students in the fields of prevention, diagnosis, and the treatment of the malignant melanoma of the skin. Material and methods. The study had been carried out from the first of February to the seventeenth of April of the ear 2013 among medical students of various fields, with the use of a survey method. Persons who took part in the survey are medical students of fields such as: nursing, obstetrics, emergency medical, and physiotherapy. Results and conclusions. Taking into consideration the results of the survey, it can be seen, that the students’ knowledge, particularly in the field of prevention, and the general knowledge of the subject is considerably high. The respondents had little knowledge when it comes to diagnosis and the treatment of the cancer. The respondents had no trouble pointing out the risk factors, as well as recognising that going to the tanning salon carries negative repercussions for health in general. Reassuming, the knowledge of the respondents is high but not satisfactory, considering that they are all people working in the medical profession, or in the least preparing for such career. The respondents have broad possibilities in the diagnosis and treatment of the malignant melanoma of the skin in the early stages or selecting the high risk groups. Nursing Topics 2014; 22 (2): 216–222